2011
DOI: 10.2486/indhealth.ms1251
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health, Suicidal Ideation, and Related Factors among Workers from Medium-sized Business Establishments in Northern Japan: Comparative Study of Sex Differences

Abstract: A questionnaire survey was conducted among 3,233 workers (2,442 males and 791 females) from 17 medium-sized business establishments in northern Japan with respect to GHQ-12 score, suicidal ideation, sociodemographic characteristics, work-associated factors, and attitude toward mental health resources. Sex differences were assessed for each questionnaire item, and logistic regression analyses were performed separately for males and females. Significant correlations between common mental disorder (CMD: GHQ-12 sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Results from the analyses we conducted support the notion that workers in certain occupations may be at higher risk of suicide due to a range of work exposures and to work related stress [Ostry et al, 2007;Bartram and Baldwin, 2010;Takusari et al, 2011].…”
Section: Discussionsupporting
confidence: 64%
“…Results from the analyses we conducted support the notion that workers in certain occupations may be at higher risk of suicide due to a range of work exposures and to work related stress [Ostry et al, 2007;Bartram and Baldwin, 2010;Takusari et al, 2011].…”
Section: Discussionsupporting
confidence: 64%
“…Previous studies have shown a significant relationship between sleep disturbance, depressive symptoms and suicidal ideation 18,32,33) . Goodwin and Marusic (2008) showed that shortened sleep was associated with a statistically significant increase in the likelihood of suicidal ideation (OR 2.5, 95%CI 1.6-3.9) and suicidal attempt (OR 3.0, 95%CI 1.4-6.4), after adjusting for confounding variables in a community population in the US 34) .…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have reported that suicidal ideation and depression were related to several potential factors, including lifestyle, job stress, and socio-demographic background 18,19) . However, there have been limited evidences focusing on this gender difference [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with Western countries, suicide in China demonstrates three unique characteristics: a) the female suicide rates are approximately the same as in the males; b) the rural suicide rates are almost double those in the urban rates; and c) there exist two peaks in the curve of suicide rates among different ages, the 15-to 34-year-olds and the 60-to 84-year-olds (Phillips et al, 2002a;Qin et al, 2001). The sex difference was found in many studies from different cultures, which showed that females had a higher incidence of suicidal ideation and suicide attempt but lower suicide rates than male in the world (He and Lester, 2001;Schaffer et al, 2000;Takusari et al, 2011).…”
mentioning
confidence: 94%